Possible inclusion in dictionaries of new words formed from the various existing procedures - Samaniego Aldazábal, José Luis (2013)
We propose that lexicographers as dictionary makers, need to include not only new words of lexicogenetic origin, but also they should consider those words formed from shortenings, foreign words, acronyms, etc. This topic is part of the preparation of a grammar that adapts the doctrine of the New Grammar of the Spanish Language to the existing grammatical tradition in Chile, thinking in particular of language teachers.